PENGEMBANGAN MODEL TUTORIAL MATEMATIKA MELALUI STUDI PEMBELAJARAN (TMSP) DI POKJAR SIDOARJO - Tri Dyah Prastiti; Jackson Pasini Mairing (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2011)
Learning achievement of Mathematics among Universitas Terbuka (UT) students generally are less satisfactory. A mathematics tutorial model by using lesson study (TMLS) was developed and evaluated. Criteria of usefulness of the lesson study is measured based on the validity, practicality and effectiveness in improving the quality of the tutorial. The study was conducted in Surabaya. The respondents consist of Mathematics learning experts, Mathematics lecturer, tutors and UTs elementary school education students. The results showed that TMLS model and its learning instruments meet the criteria of validity, practicality and effectiveness. It can be seen from the results of the implementation TMLS model that showed some advantages, such as (a) good response of the students toward TMLS model, (b) the TMLS model was suitable with the tutorial basic principle that is students independence, (c) the TMLS model increased students mastery and thinking level at the mathematic modules, (d) the TMLS model had motivated students to be active in finding the deeper understanding of the subjects, (e) the TMLS model had motivated students to improve their meta cognitive knowledge, (f) The tutors role in the implementation of the TMLS model was suitable with the main function of tutor, and (g) the learning syntax of the TMLS model had motivated the students to be active in learning and developing their mathematics communication.